Efektivitas Presensi Online Dalam Meningkatkan Kinerja ASN Di Kecamatan Banjar Kota Banjar - Susy Mardila (Politeknik Kampar, 2023)
The Effectiveness of Online Presence in Improving ASN Performance in Banjar District, Banjar City. Susi Mardila. Under the guidance of Dr. H. Enas, SE., M.M as supervisor I and Dr. Hj. Aini Kusniawati, MM as supervisor II. This research is motivated by the results of observations which prove that the implementation of online attendance in the Banjar District has an impact on improving the performance of ASN employees in the Banjar sub-district. For this reason, this study aims to determine the effectiveness of online attendance in improving ASN performance in Banjar District, Banjar City. The method used in this research is a qualitative research method. The results of the study concluded that the implementation of online presence has a positive impact on improving employee performance both in quality, quantity and time utilization. Because with online presence employees are more disciplined and better able to take advantage of working time because they cannot improve their workplace before working hours end. Through online attendance, employees cannot manipulate any data, especially attendance data, because it has been set in such a way as to optimize working time. Obstacles encountered in improving the performance of ASN in Banjar District, Banjar City, are problems with funds or budget, human resources and understanding of the main tasks and functions of the employees themselves. is by increasing the budget, increasing the competency of ASN both through related agencies and through individual wishes